OPTIMIZATION OF RESEARCH AND DEVELOPMENT AGENCY'S RESEARCH RESULTS INTO THE FORM OF DEVELOPMENT PRODUCTS - Dani, Fatimatuz Zahro Diah Putri; Khoiriyani, Fauziah (Universitas Negeri Yogyakarta, 2022)
This study aims to mapping and identifying research and use of research into development products carried out by the Research and Development (R&D) Agency of the Ministry of Religion during 2018-2020. In addition, this study also aims to analyze what obstacles can hinder and what solutions can be given in optimizing the utilization of the research results of the R&D Ministry of Religion in product development. The research method used in this study is a qualitative method, with typology method and analyzed using qualitative descriptive. Data collection used document studies as secondary data and in-depth interviews with several stakeholders as primary data. The scope of this research are the central work unit and regional work unit in the Ministry of Religion whose main task is to conduct R&D. The findings of this study indicate that the utilization of R&D of the Ministry of Religion in the form of product development has not been optimal yet. This is indicated by data showing that from 330 studies conducted, 25% of these studies have been developed into a product while the remaining 75% has not been utilized as a product development. Five classifications of constraints were also identified in this study, financial, operational, socialization, human resources and policy constraints. Human resource constraints and policy constraints are the most inhibiting factors in the use of research. Once these constraints are identified.